Feasibility of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) antigen self-testing in school and summer camp attendees - Colom-Cadena, Andreu; Martínez-Riveros, Héctor; Bordas, Anna; Alonso-García, Lucia; Montoro-Fernández, Marcos; Romano-deGea, Pol; Vidal-Alaball, Josep; Solà-Segura, Elisabet; Llibre, Josep M.; Revollo, Boris; Casabona, Jordi; Agustí, Cristina (Frontiers in Pediatrics, 2023)
Background: SARS-CoV-2 screening is one of the pillars of non-pharmaceutical preventive strategies to early identify and isolate infected individuals and therefore decrease community incidence. Methods: We assessed the feasibility of severe acute respiratory syndrome coronavirus 2 self-testing with antigen-detecting rapid diagnostic tests in attendees of educational settings. Results: A total of 305 students (88.15%) and 41 staff (11.85%) from 9 to 56 years old participated in the self-testing procedure and answered the survey at the end of the study. 91.3% (n=313) did not need help, 96.1% of participants reported the same outcome as the healthcare workers. 94.5% strongly or slightly agree with the statement “I would repeat the experience”. Conclusion: The study demonstrates that self-testing is acceptable and usable in children, adolescents and adults when the epidemiological situation may require a systematic screening of these populations, although supervision by health care or previously trained personnel is recommended for younger age groups